2023
DOI: 10.3389/fmicb.2022.1037733
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal observation of viral load in patients infected with Omicron variant and its relationship with clinical symptoms

Abstract: ObjectiveIn 2022, a new coronavirus variant (Omicron) infection epidemic broke out in Shanghai, China. However, it is unclear whether the duration of this omicron variant is different from that of the prototype strain.MethodsWe retrospectively analyzed 157 cases of Omicron variant infection in Taizhou Public Health Center from March 29, 2022, to April 18, 2022, and observed the dynamics of nucleic acid Ct values during the admission and discharge of patients. Clinical and laboratory indicators of these patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…With the original SARS-CoV-2 strain, Ct values tended to peak around the time of symptom onset or even slightly before. 14 However, the pattern right-shifted with the omicron variant; viral burden now tends to peak 1-3 days after symptom onset, 15,16 which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…With the original SARS-CoV-2 strain, Ct values tended to peak around the time of symptom onset or even slightly before. 14 However, the pattern right-shifted with the omicron variant; viral burden now tends to peak 1-3 days after symptom onset, 15,16 which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Limited by the sampling before symptom onset, it is still uncertain what the viral loads were in oropharyngeal and nasopharyngeal sites before symptom onset. However, it can be preliminarily speculated that the viral load in oropharyngeal specimens may have reached its peak before symptoms appeared, as multiple studies have shown that Omicron is highest 2–5 days after symptoms [ 20 , 21 ] and declines significantly after around 10 days [ 22 ], with the virus being detected early in the oropharynx, but at higher and more persistent levels in the nose [ 23 ]. Similarly, for XBB.1*cases, we observed that the clearance period of nasopharyngeal swabs was 11.87 days, which was shorter than that of BA.5* infections.…”
Section: Discussionmentioning
confidence: 99%
“…Morang'a et al [43] indicate in their 3). Other studies have also reported that Omicron (B.1.1.529.2) infections are associated with severe forms of infection with reported high viral loads [46,47] and severe symptoms [48]. Te increased infectiousness of the Omicron variant (B.1.1.529.2) stems from immune escape due to altered spike-in antigens [49,50].…”
Section: Sars-cov-2 Circulating Genotypes Te Fndings Of This Study In...mentioning
confidence: 99%